2015
DOI: 10.1016/bs.acr.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Control of CD8 T-Cell Infiltration into Tumors by Vasculature and Microenvironment

Abstract: CD8 T-cells are a critical brake on the initial development of tumors. In established tumors, the presence of CD8 T-cells is correlated with a positive patient prognosis, although immunosuppressive mechanisms limit their effectiveness and they are rarely curative without manipulation. Cancer immunotherapies aim to shift the balance back to dominant anti-tumor immunity through antibody blockade of immunosuppressive signaling pathways, vaccination, and adoptive transfer of activated or engineered T-cells. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 257 publications
4
111
0
Order By: Relevance
“…These CXCR3-ligands constitute the major chemokine axis enabling tumor infiltrating lymphocyte (TIL) entry into tumors, 24 and have been associated with TIL infiltration in several tumor models. 25 Moreover, increased CCL2 can also trigger T-cell recruitment through the macrophage ability to engulf and present antigens using MHC molecules, especially in the presence of trastuzumab by boosting antibody-dependent cellular phagocytosis-mediated killing of cancer cells. 19 Subsequently, the IFN-γ produced by recruited stimulated lymphocytes, which has been described to be crucial for Th1 immunity and trastuzumab response, 26 would in turn induce CXCLs in tumor cells followed by improved T cell-trafficking and maintenance of immune-enriched TME.…”
Section: Discussionmentioning
confidence: 99%
“…These CXCR3-ligands constitute the major chemokine axis enabling tumor infiltrating lymphocyte (TIL) entry into tumors, 24 and have been associated with TIL infiltration in several tumor models. 25 Moreover, increased CCL2 can also trigger T-cell recruitment through the macrophage ability to engulf and present antigens using MHC molecules, especially in the presence of trastuzumab by boosting antibody-dependent cellular phagocytosis-mediated killing of cancer cells. 19 Subsequently, the IFN-γ produced by recruited stimulated lymphocytes, which has been described to be crucial for Th1 immunity and trastuzumab response, 26 would in turn induce CXCLs in tumor cells followed by improved T cell-trafficking and maintenance of immune-enriched TME.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VEGF also contributes to form an immunosuppressive environment through inhibiting CTL migration to the tumor site. 96 Previous studies have shown that angiogenesis inhibitors normalize the vessels inside the tumor for effective drug delivery and convert the tumor microenvironment from immunosuppressive to an active state. 97,98 However, antiangiogenic agents tend to suppress the tumor growth rather than eliminate tumor cells and single-agent treatment is not supposed to produce a durable antitumor response.…”
Section: Combined With Targeted Therapymentioning
confidence: 99%
“…E-selectin expression, although higher than that of normal tissue, was not significantly influenced by adaptive immunity. Increased HR ligand expression is associated with increased T-cell representation in the tumor microenvironment and improved tumor control (41). Collectively these studies suggest that HR ligand expression on most tumors limits CD8 + effector T-cell entry, but can be enhanced by augmenting endogenous immunity, directly activating tumor vascular EC, or manipulating the immunosuppressive tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%